Analisis Keputusan Pembelian Susu Sapi Perah Pak Dul - Datul Amaliya, Iva; Purwandhini, Ari Septianingtyas (Program Studi Agribisnis, 2024)
Jember Regency has an area with potential dairy cattle production centers, namely in Kemuning Lor Village, Arjasa District. Therefore, dairy farming needs to be studied in depth. The aim of this research is to determine the factors that influence consumers' purchasing decisions for